2015
DOI: 10.1016/j.ccell.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

A DNA Hypomethylation Signature Predicts Antitumor Activity of LSD1 Inhibitors in SCLC

Abstract: Epigenetic dysregulation has emerged as an important mechanism in cancer. Alterations in epigenetic machinery have become a major focus for targeted therapies. The current report describes the discovery and biological activity of a cyclopropylamine containing inhibitor of Lysine Demethylase 1 (LSD1), GSK2879552. This small molecule is a potent, selective, orally bioavailable, mechanism-based irreversible inactivator of LSD1. A proliferation screen of cell lines representing a number of tumor types indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
375
3
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 431 publications
(395 citation statements)
references
References 46 publications
15
375
3
2
Order By: Relevance
“…ChIP-seq and BRET assay data suggest that loss of KDM1A upon inhibitor treatment is a context-specific phenomenon that does not globally affect KDM1A chromatin association. A recent study of KDM1A-binding sites in small cell lung cancer models upon KDM1A inhibitor treatment did not report any changes in chromatin association (42). Our data support the concept that inhibitormediated loss of KDM1A results in more pronounced changes in H3K4me2 levels as well as transcriptional activation as compared with mere KDM1A inhibition.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…ChIP-seq and BRET assay data suggest that loss of KDM1A upon inhibitor treatment is a context-specific phenomenon that does not globally affect KDM1A chromatin association. A recent study of KDM1A-binding sites in small cell lung cancer models upon KDM1A inhibitor treatment did not report any changes in chromatin association (42). Our data support the concept that inhibitormediated loss of KDM1A results in more pronounced changes in H3K4me2 levels as well as transcriptional activation as compared with mere KDM1A inhibition.…”
Section: Discussionsupporting
confidence: 86%
“…While our manuscript was in preparation, small cell lung cancers of the neuroendocrine subtype were reported to be dependent on KDM1A (42). In this study, irreversible KDM1A inhibitors were used across a large cancer cell panel and broad responses in AML were noted, in agreement with our data.…”
Section: Discussionsupporting
confidence: 85%
“…More recently, proteomic profiling studies have identified alterations in SCLC that comprise therapeutically viable targets, including PARP1 and DNA repair proteins (82,83). Also, Mohammad and colleagues described the histone demethylase lysine demethylase 1 (LMD1) as a therapeutic target for SCLC (84). It is noteworthy that the roles of these aforementioned alterations and targets in normal and premalignant phases of SCLC development are still poorly comprehended.…”
Section: Sclc Pathogenesismentioning
confidence: 99%
“…Lessons can be learned from these studies where the basic concept was that inhibition of transcription by DNA methylation or by elimination of the active acetyl mark resulted in silencing of tumor suppressors (p21, BRACA1, p53). In fact, the changes in DNA methylation that occur in cancer are complex, with large domains being hypomethylated [1]. Moreover, multiple enzymes can deacetylate histones, thus affecting multiple networks, but which networks and which HDACs are important for inhibition of cancer growth is relatively unexplored.…”
Section: Background and Conceptsmentioning
confidence: 99%
“…Documenting inhibitor effects on gene expression in a wide range of cell types has been used to good effect in understanding the action of the bromodomain and extraterminal proteins inhibitors which inhibit binding of the BRD bromodomain-containing proteins which are readers of acetylated histones. Defining the cancer type for sensitivity to inhibitors of the LSD1 (KDM1A) H3K4me2 demethylase has also been applied effectively to the selection of small cell lung cancer and acute myeloid leukemia as cancer targets [1].…”
Section: Background and Conceptsmentioning
confidence: 99%